LEADERSHIP FORGED IN CRISIS. Issue 91 (13th September 2018) - Koehn, Nancy
Abstract: Five great leaders from history (Abraham Lincoln, Frederick Douglass, Ernest Shackleton, Rachel Carson, and Dietrich Bonhoeffer), according to Koehn, had their leadership forged in crisis. She writes that "leaders can emerge from many different backgrounds, genders, races, and personality types." Each leader was made, not born, and faced varying degrees of hardship, from Douglass' escape from slavery to Carson's hardscrabble upbringing. She writes, "Perhaps most significant, each of the five leaders embraced a mission uniquely his or her own." Koehn elaborates on Carson's sensitivity and the ingenuity of Lincoln and Douglass. She concludes that "the very way that each lived was an act of leadership unto itself, whose impact resonates—and calls to us—in the early 21st century."